Cooking at home: A multimodal narrative analysis of the Food Network. (June 2017) - Matwick, Kelsi; Matwick, Keri
Abstract: This article explores the mediated discourses of food and gender in a multimodal narrative analysis of two Food Network instructional cooking shows hosted by female protagonists. Through a discussion of the openings and closings, side-narratives and evaluations, this article shows how multimodality advances the cooking show narrative. In examining the presentation of the women cooks in the context of their homes and family, the analysis illustrates how the mediated context facilitates the transition of women from underappreciated and expected caretakers in the kitchen to confident and empowered agents.